ECONOMIC ASPECTS OF WATER MANAGEMENT - Bajčetić, Marko (Economics of Agriculture, 2018)
Water is the most significant natural resource. There is no life without water. Throughout the history, relation to water has been changed, during which water, first seen only as a natural resource, has also become an economic good. Depending on the type of water in consumption, it can be comprehended as an absolute public asset, a public asset or a private property. Water managements goal is to attain the efficiency in water services, through which the quality and the quantity of water is being changed, in order to satisfy the consumers (population, agriculture and industry). The creation of necessary conditions, such as income achievement through taxes and atonement, provide both public and private water consumption. In the view of the fact that water management is an infrastructural activity, it ought to be tailored in the accordance with transitional processes. The important task of water management is the integration of EU WFD, especially in handling river basins.